Let Us Rethink Prescribing Education Together - Joon Soo Park (Asia Pacific Journal of Health Management)
Prescribing education is central to patient safety and effective clinical practice, yet it remains fragmented across health professions, often taught in disciplinary silos without sufficient interprofessional integration. Drawing on qualitative and cross-sectional studies in Australian dental prescribing education, including student interviews and national surveys, this paper highlights significant gaps between theoretical learning and clinical application, particularly in areas such as antimicrobial stewardship. These gaps reflect broader systemic issues, where limited collaboration between prescribers, pharmacists, and other healthcare professionals undermines safe prescribing practices. We argue that prescribing should be understood as a shared, patient-centred process requiring intentional, interprofessional education. To address these challenges, internationally aligned frameworks, integrated curricula, and collaborative assessment models that reflect real-world complexity. Preparing students for teamwork rather than isolated competencies will foster safer, more effective prescribing decisions and improve patient outcomes globally.